Analysis of the characteristics of blood lipid metabolism in twin pregnancy. (January 2023) - Lou, Yanqin; He, Pei; Jiang, Huijun; Xiang, Li; Gao, Xuemei
To investigate the characteristics of blood lipid metabolism in twin pregnancy combined with gestational diabetes mellitus (GDM) or pregnancy-induced hypertension (PIH). This study retrospectively analyzed 96 cases of twin pregnancy and 232 cases of full-term singleton pregnancy. General data and blood lipid levels, including triglyceride (TG) and total cholesterol (TC), between twin and singleton pregnancies were compared. Blood lipid levels between GDM (PIH) and non-GDM (non-PIH) groups in twin pregnancy were compared. The TG level for twin pregnancy was higher than that for singleton pregnancy (p<0.05), while there was no significant difference in the TC level between them (p>0.05). The TG level in the GDM group was higher than that in the non-GDM group (p<0.05), while the TC level in the GDM group was not different from that in the non-GDM group (p>0.05). The TG level in the PIH group was higher than that in the non-PIH group (p<0.05), while there was no difference in the TC level between them (p>0.05). Logistic regression analysis showed that age was a risk factor for GDM and PIH in singleton and twin pregnancies. The lipid levels in twin pregnancy increased with the increase of gestational age, and the TG level in twin pregnancy complicated with GDM or PIH was higher than that in twin pregnancy without GDM or PIH, indicating that the blood lipid metabolism was related to the occurrence of GDM and PIH in twin pregnancy to some extent.